The effect of a social skills training that employs structured group encounter - Nozaki, M.; Mizuochi, F. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Social skills are acquired by (1) being taught, (2) imitating, (3) making attempts, and then (4) learning from the results. Structured Group Encounter (SGE) contains these elements in its exercises and thus enables direct contact with different ways of selfexpression other than one`s own through its exercises and sharing (conversation in a group). It is also considered to grow the social skills effectively in the course of intensive group experiences. Although the junior period is a great occasion to foster the social skills, some reports say that recently some junior athletes don`t benefit from their sports activities in terms of the social skills. The object of this study is to examine whether a long-term social skills training that employs SGE for junior alpine skiers is effective for improving their social skills.